A Model for Enhancing Academic Competence Among Lecturers in Police Training Centers - Wiboon Wiwithkhunakorn; Kittachet Krivart; Arpaporn Sookhom; Mahdee Champeephan; Shubham Pathak (Emerging Science Journal, 2025)
This research aims to investigate the level and factors of academic competence among lecturers at the Police Training Center, Region 1-9, Royal Thai Police. This research aims to develop and validate a model for enhancing the academic competence of lecturers. This research employed a mixed-methods quantitative and qualitative approach. The data were collected and analyzed using descriptive statistics, mean, percentage, standard deviation, and structural equation model (SEM). The findings include that the lecturers' level of academic competence was high. Factors affecting lecturers' academic competence include personal, organizational, and environmental factors. Development of Academic Competence of Lecturers: 1) Personal Factors. Lecturers should develop expertise in the field they teach, skills in knowledge transfer, research, and data analysis, as well as enhance their ethics and adherence to codes of conduct. 2) Organizational factors. The organization should improve its structure and policies to support effective teaching and learning, develop personnel management systems and incentive measures, provide up-to-date learning materials, and foster networks. Academic cooperation: 3) Factors related to the working environment should include developing infrastructure and facilities, creating a good atmosphere, reducing stress, and promoting teamwork. Confirming that the academic competency development model for teachers at the Police Training Center, Region 1-9.